Enhancing Employability Of Professional Self-Employed In Business Management Through Mapping Occupational Standards In Entrepreneurship Within The Indonesian Qualification Framework - Surono, Surono (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
This research investigates the enhancement of employability for professional self-employed individuals in business management by mapping occupational standards in entrepreneurship within the Indonesian Qualification Framework (IQF). The study aims to identify the types of entrepreneurship occupations and their corresponding competencies to bridge the gap between formal education and industry needs. Utilizing a combination of the Mapping Study method and Rapid Assessment Process (RAP), the research collects and analyzes secondary data from national employment databases, industry reports, academic publications, and government documents. The findings reveal a comprehensive occupational matrix detailing the progression from foundational to advanced entrepreneurial roles, each with specific core and elective competencies. These competencies are crucial for roles emphasizing strategic leadership and business development. The study provides a structured approach for developing targeted training programs and vocational education policies that align with industry requirements, ultimately enhancing the employability of self-employed business professionals. Recommendations include aligning training programs with industry needs, enhancing access to certification programs, increasing awareness of occupational standards, incorporating practical experience, and standardizing competency descriptions across regions and institutions.